(untitled) (Journal of history, 2022)
The culmination of world imperialism in the late 19th and early 20th centuries. led to a change in the foreign policy of the great powers. Each empire, on the way to solving its foreign policy problems, developed international integration in every possible way, established close ties with other states. One of them was the foreign policy of the Ottoman Empire in Central Asia, which was distinguished by its spiritual and ideological content. XIX-XX centuries the idea of the unity of the Turkic peoples prevailed, the spirituality and culture of which was considered one, had not only spiritual and cul- tural, but also political and ideological significance. The article examines the spiritual and ideological content of the policy of the Ottoman Empire in Central Asia at the beginning of the 20th century. The political significance of the spiritual and cultural unity of the Turkic peoples is revealed. The history of political ties based on the ideology of Islamic unity and Pan-Turkism on the part of the Ottoman Empire is investigated. One of the main tasks of the article is to consider the political aspect of the spiritual and cultural association, which is the beginning of the ideological trend known in world his- toriography as “Pan-Turkism”. It also analyzes the Pan-Islamic policy of the Ottoman Empire among the Muslim peoples of Central Asia. Key words: Central Asia, Turkestan, Ottoman Empire, Pan-Turkism, Pan-Islamism, Foreign policy, Political processes